2000
DOI: 10.1086/303085
|View full text |Cite
|
Sign up to set email alerts
|

An Isochore Transition in the NF1 Gene Region Coincides with a Switch in the Extent of Linkage Disequilibrium

Abstract: Whole-genome association studies will be a powerful tool to identify genes responsible for common human diseases. A crucial task for association-mapping studies is the evaluation of the relationship between linkage disequilibrium (LD) and physical distance for the genomic region under study. Since it is known that the extent of LD is nonuniformly distributed throughout the human genome, the required marker density has to be determined specifically for the region under study. These regions may be related to iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 21 publications
3
37
0
2
Order By: Relevance
“…The odds ratio increases with increasing repeat tract length from 1.313 for intervals containing repeats of greater than 45 bp long up to 1.901 for intervals with repeats of 200 bp and over. MIR and LTR repeats were also associated, together with G+C content, supporting previous observations of isochore transitions that coincide with a switch in the extent of LD (Eisenbarth et al 2000(Eisenbarth et al , 2001.…”
Section: Resultssupporting
confidence: 88%
“…The odds ratio increases with increasing repeat tract length from 1.313 for intervals containing repeats of greater than 45 bp long up to 1.901 for intervals with repeats of 200 bp and over. MIR and LTR repeats were also associated, together with G+C content, supporting previous observations of isochore transitions that coincide with a switch in the extent of LD (Eisenbarth et al 2000(Eisenbarth et al , 2001.…”
Section: Resultssupporting
confidence: 88%
“…By contrast, she found that, in D. yakuba, in which the recombination rate is more than ten times higher in this region, substitutions are GC-biased in both synonymous sites and non-coding DNA. Such a neutral effect of recombination has also been demonstrated in the nematode (Marais et al, 2001), and it has been proposed to occur in a wide range of eukaryotic organisms, such as yeasts (Baudat & Nicolas, 1997 ;Gerton et al, 2000 ;Birdsell, 2002), mice (Perry & Ashworth, 1999) and humans (Eyre-Walker, 1993 ;Eisenbarth et al, 2000 ;Yu et al, 2001;Fullerton et al, 2001 ;Galtier et al, 2001).…”
Section: Fnop-gc Andmentioning
confidence: 95%
“…We observed this correlation both when we divided the genome into windows of 100-1000 kb and also when we compared sequence characteristics of "hotspots" for the breakdown of linkage disequilibrium and other genomic regions. GC content has previously been associated with recombination rate and linkage disequilibrium (Eisenbarth et al 2000;Yu et al 2001), and the association could occur either because GC-rich sequences are more prone to recombination or because recombination leads to mutation from A/T to G/C base pairings more often than to mutations in the opposite direction (Huang et al 2005). The association between sequence polymorphism and linkage disequilibrium could occur because recombination events are mutagenic, because regions of lower linkage disequilibrium are likely to descend from a more distant ancestor so that they have undergone more rounds of both mutation and recombination, or even because some regions of strong disequilibrium result from selective sweeps and show limited diversity (Hudson 1990;Nachman et al 1998).…”
Section: Genome Research 1529mentioning
confidence: 99%
“…Although this relationship has been examined in several previous studies (for examples, see Eisenbarth et al 2000;Yu et al 2001;Dawson et al 2002), these have focused on relatively small amounts of data. The results of these initial studies show that linkage disequilibrium is strongly influenced by the local recombination rate (Dawson et al 2002) and correlated with other factors that are associated with local recombination rates, such as GC content, gene density, and the presence of SINE or Alu repeats (Fullerton et al 2001;Yu et al 2001;Dawson et al 2002).…”
mentioning
confidence: 99%